Interfacial Engineering of CdO-CdSe 3D Microarchitectures with insitu Photopolymerized PEDOT for an Enhanced Photovoltaic Performance - Lim, Iseul; Shinde, Dipak V.; Patil, Supriya A.; Ahn, Do Young; Lee, Wonjoo; Shrestha, Nabeen K.; Lee, Joong Kee; Han, Sung-Hwan (WILEY, 2015)
In the present work, porous 3D CdO-microstructured electrode obtained by pyrolysis of 3D CdCO3 microstructures is self-sensitized with CdSe using an ion exchange reaction. After sensitization, an interfacial treatment of the CdO-CdSe interface is performed by depositing a thin film of PEDOT using a photoinduce polymerization route. The microstructured electrode before and after interfacial treatment is characterized using field-emission scanning microscope, energy dispersive X-ray analyzer, contact angle measurement, UV-Visible absorption spectrophotometer and X-ray photoelectron spectrometer. After constructing a liquid junction solar cell with a Pt counter electrode, the photovoltaic performance and interfacial charge transfer kinetics across the CdO-CdSe interface before and after PEDOT treatment are investigated. The results exhibit an improved interfacial charge-transfer resistance after the PEDOT treatment, which leads to enhance the short-circuit current by 15.81% and the power conversion efficiency by 19.82%.
Keywords: SENSITIZED SOLAR-CELLS; TICL4 TREATMENT; BUFFER LAYER; TIO2 FILMS; EFFICIENT; PHOTOANODES; DYNAMICS